30‐3: Deciphering ELA via Transient Reflectance Analysis. Issue 1 (2nd June 2017) - Wong, Vernon K.; Yu, Miao; Pan, Wenkai; Song, Ruobing; Suresh, Akhilesh K.; Choi, Insung; Im, James S.
Abstract : We have experimentally investigated excimer‐laser‐induced melting of ELA‐prepared polycrystalline Si films using in situ transient reflectance and transmission analysis. The results clearly reveal that melting can proceed in a predominantly 2‐D manner for these thin and small‐columnar‐grained polycrystalline Si films. Based on considering the presently and previously obtained experimental results, as well as considering the thermal, thermodynamic, and kinetic aspects of the melting‐transition‐relevant details, we present a model that consists of (1) the prompt initiation of melting taking place at grain boundaries and junctions, and (2) the melting proceeding laterally into the transiently superheated interior of the grains. We briefly discuss how the present model can account for the evolution of columnar‐grained polycrystalline Si films observed during ELA processing of the films.